Avaliação da vancocinemia em pacientes atendidos em um hospital universitário do Rio Grande do Sul - Giacomolli, Cláudia (2013)
Vancomycin is one of the most extensively used antibacterial agents for the treatment of severe gram positive infections including methicillin-resistant Staphylococcus aureus. It is also known that the use of this antimicrobial is a risk factor for subsequent colonization or infection with vancomycin-resistant Enterococcus (VRE). This retrospective observational study was to evaluate the results of vancocinemias that were conducted in adult and pediatric patients hospitalized in the period january to november 2012 at the University Hospital of Santa Maria (HUSM). Were evaluated 353 vancocinemias performed in 115 patients. Of the total, 180 vancocinemias were collected in the TROUGH, of these 150 (83.33%) were above the recommended range, 20 (11.11%) were within the expected values and 10 (5.56%) showed lower than expected. The review was carried out in 26 patients at the PEAK, 15 (57.69%) showed lower serum concentrations recommended, 5 (19.23%) were within the range and 6 (23.08%) had values greater than those expected. The remaining 147 (41.64%), was not collected in strips of PEAK and TROUGH. These data confirm the importance and necessity of conducting a routine therapeutic monitoring of vancomycin, through the creation and implementation of a collection routine.